2016
DOI: 10.1016/j.ecoleng.2015.05.044
|View full text |Cite
|
Sign up to set email alerts
|

Aridland constructed treatment wetlands I: Macrophyte productivity, community composition, and nitrogen uptake

Abstract: Publisher's copyright statement: NOTICE: this is the author's version of a work that was accepted for publication in Ecological Engineering. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be re ected in this document. Changes may have been made to this work since it was submitted for publication. A de nitive version was subsequently published in Ecological Engineering, December 2016December , 97, 64… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 26 publications
3
28
0
Order By: Relevance
“…CW planted with a polyculture of five ornamental flowering species removed up to 92% of PO4 3and 84% of NH4 + (Calheiros et al, 2015). Another study also found higher N removal in wetland with diverse plant communities than monotypic stands (Weller et al, 2015). Two large-scale CWs in South Florida achieved 77% to 84% of TP reduction over long term operation (Pietro and Ivanoff, 2015).…”
Section: Wetlands For Nutrient Removalmentioning
confidence: 85%
“…CW planted with a polyculture of five ornamental flowering species removed up to 92% of PO4 3and 84% of NH4 + (Calheiros et al, 2015). Another study also found higher N removal in wetland with diverse plant communities than monotypic stands (Weller et al, 2015). Two large-scale CWs in South Florida achieved 77% to 84% of TP reduction over long term operation (Pietro and Ivanoff, 2015).…”
Section: Wetlands For Nutrient Removalmentioning
confidence: 85%
“…According to Chyan, Lu, Shiu and Bellotindos (), a TP removal rate of 93% in CWs with substrate could be attributed to the processes of retention and adsorption of particulate material. Besides the retention and absorption of particulate forms of N and P, some authors reported that the substrate itself favours the precipitation and sedimentation of organic and inorganic particles (Brix, Koottatep & Laugesen, ; Kumar & Zhao, ; Weller et al., ). In the CWs without substrates, the retention of particulate material, removal of TSS, and the retention of TP and TKN were lower than in the CWs with substrates, probably because the particulate material is only retained by sedimentation and/or by the roots of the free‐floating macrophytes (Henares & Camargo, ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the contribution of Phragmites australis to the removal of total phosphorus was less than 5% compared to a system without macrophytes (Vymazal, ). In the case of domestic wastewater, the reduction of inorganic nitrogen by emergent macrophytes was only 7% (Weller, Childers, Turnbull & Upham, ). Vymazal () reported less than 5% of N and P stocked in the plant biomass in a CW that employed emergent macrophytes.…”
Section: Introductionmentioning
confidence: 99%
“…In our five years of studying the Tres Rios constructed treatment wetlands ecosystem, we have documented the productivity and nutrient assimilation capacity of the wetland plants and soils (Weller et al. ). We have also documented plant‐mediated control of surface water hydrology, for the first time in any wetland, in the form of a “biological tide” that is driven by plant transpiration that brings both water and nutrients from the open water areas into the vegetated wetland, where near‐complete nutrient removal takes place (Sanchez et al.…”
Section: Applying the Framework: Actions Outcomes And The Importancmentioning
confidence: 99%